2024
DOI: 10.3390/s24082663
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Distributed Digital Twin Framework for Predictive Maintenance in Industrial Internet of Things (IIoT)

Ibrahim Abdullahi,
Stefano Longo,
Mohammad Samie

Abstract: This study uses a wind turbine case study as a subdomain of Industrial Internet of Things (IIoT) to showcase an architecture for implementing a distributed digital twin in which all important aspects of a predictive maintenance solution in a DT use a fog computing paradigm, and the typical predictive maintenance DT is improved to offer better asset utilization and management through real-time condition monitoring, predictive analytics, and health management of selected components of wind turbines in a wind far… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Within the state of the art, it is observed that most of the works presented by other authors do not follow a standard for the design of DT architectures; however, as a developing technology, several industries and universities have focused their attention on it. For the design of 3D environments, several CAD version 2022 softwares are used: among the main ones are Blender and Solid Work; for communication, the most used protocols are OPC UA, TCP/IP, AMQP, MODBUS, and MQTT; and in the physical environment, the process data are obtained by PLCs or embedded systems [20,29,31,32]. In addition, the integration of several technologies is evidenced to enhance the characteristics of the DT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the state of the art, it is observed that most of the works presented by other authors do not follow a standard for the design of DT architectures; however, as a developing technology, several industries and universities have focused their attention on it. For the design of 3D environments, several CAD version 2022 softwares are used: among the main ones are Blender and Solid Work; for communication, the most used protocols are OPC UA, TCP/IP, AMQP, MODBUS, and MQTT; and in the physical environment, the process data are obtained by PLCs or embedded systems [20,29,31,32]. In addition, the integration of several technologies is evidenced to enhance the characteristics of the DT.…”
Section: Resultsmentioning
confidence: 99%
“…One of the areas where DTs are used is in maintenance, where several investigations have been carried out. In [20][21][22], they present a DT to perform the predictive maintenance of a wind turbine and reliability in floating offshore wind turbines (FOWTs). The architecture presents a distributed DT with IIoT, machine learning (ML), MQTT, and fog computing to offer the better utilization and management of assets through real-time condition monitoring, predictive analysis, and the health management of selected wind turbine components in a wind farm.…”
Section: Related Workmentioning
confidence: 99%